Rehabilitation Impact of Vivifrail Exercise Program Type C on the Cognitive Function of Pre-Frail Elderly People in the Community - Soenarti, Sri; Lestari, Dwi Indriani; Nugroho, Muhammad Barlian; Lestari, Harien (Folia Medica Indonesiana, 2024)
Highlights: 1. This study emphasizes the importance of providing physical exercises to pre-frail elderly individuals, especially in a community setting. 2. This study establishes a foundation for future research to explore the relationship between physical exercise, particularly the Vivifrail Type C Protocol, and cognitive function in pre-frail elderly individuals. Abstract Frailty is a clinical syndrome that increases vulnerability, potentially leading to disability or death. The pre-frail phase is ideal for preventing frailty and improving quality-adjusted life years, particularly through physical exercises that reduce the risk of dementia and cognitive impairment. Multicomponent exercises, such as the Vivifrail Exercise Program, may enhance cognitive function and daily independence by preventing and mitigating frailty through tailored routines. However, its impact on cognitive function in pre-frail elderly people had not been well studied. This study aimed to determine the effect of the Vivifrail Exercise Program Type C on the cognitive function of pre-frail elderly people. This study was a quasi-experiment with a non-randomized control group pretest-posttest design. The sample was chosen by the quota sampling method. Twenty-seven subjects were analyzed, comprising 16 individuals in the exercise group and 11 individuals in the control group. The exercise group participated in the Vivivfrail Type C Exercise Program, with 45-minute sessions conducted biweekly for 12 weeks. The evaluated parameters included the Montreal Cognitive Assessment-Indonesian Version (MoCA-INA) and the Loewenstein Occupational Therapy Cognitive Assessment (LOTCA). The statistical analysis utilized the Kruskal-Wallis test, followed by the post-hoc Mann-Whitney test and independent t-test (p<0.05). A path analysis was performed using simple linear regression. The subjects' average ages were 72.2 years in the control group and 67.47 years in the exercise group. The Vivifrail Exercises Program Type C significantly improved the MoCA-INA scores from 20.25 to 24.06. It also increased the LOTCA scores in several domains, i.e., thinking operations and visual perception. The exercise group demonstrated more improvement than the control group (p=0.032). An enhancement in cognitive function was particularly observed in elderly women with pre-frailty. In conclusion, the Vivifrail Exercise Program Type C can help improve the cognitive function of the elderly within the community.